Cognitive Style and Communicative Competence of Students - Kostruba, Nataliia; Hoshovskiy, Yaroslav (Psychological Prospects Journal, 2020)
The aim of this research is to analyze the relationship of cognitive styles with the communicative competence of the student. Cognitive style as an individual way of processing information is associated with all areas of human life: management, psychotherapy, education, etc. Cognitive styles are the best indicators of individual success, decision-making, etc. We hypothesized that there is a connection between cognitive styles and communicative competence as a construct. Empirically studied three types of cognitive-stylistic organization of personality (field dependence – field independence; analytical-synthetic; flexibility-rigidity). The results showed that half of the respondents demonstrate competent reactions in communication, the ability to adequately respond to the behavior of others in different situations. Other students showed aggressive or dependent behavior, indicating a low level of communicative competence of students. Students often have such cognitive styles as field independence and flexibility of thinking. Empirical analysis revealed statistically significant relationships of response types in communication with such cognitive styles as flexibility-rigidity. We did not find statistically significant relationships between communicative competence and cognitive styles field dependence-field independence and analytical-synthetic. The results show that high rates of aggression in communication are related with high rates of rigidity of thinking. We also found a weak correlation between dependent behavior in communication and indicators of flexibility of thinking. The prospects for further research are the analysis of the relationship of communicative competence with other cognitive styles and in other age categories.